BENTUK PERLINDUNGAN HUKUM TERHADAP KEKAYAAN MINYAK DAN GAS BUMI SEBAGAI ASET NEGARA MELALUI INSTRUMEN KONTRAK - Kurniawan, Faizal (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
State has the power to manage natural resources for the sake of social justice, the general welfare and are used as much as possible the greatest benefit for the greatest welfare of people. Contract law is the main instrument used to protect the state assets including oil and gas. Production Sharing Contract as a legal safeguard for oil and gas, is a fundamental pillar in the effort and utilization management activities of oil and gas. In the contracts involving the Government, called government contract, there is a unique characteristic which is not entirely subject to private law. In principle, the state should not be harmed, called as state immunity. This principle also applies universally in the interest of protecting the state assets. Keywords: Production Sharing Contract, Government Contract, State Immunity, Protection of State Assets Clause.